Peranan Lembaga Pembinaan Dan Pengembangan Al-Islam dan Kemuhammadiyahan (LP2AIK) Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Bagi Mahasiswa Poltekkes Muhammadiyah Makassar - Irsyadah Ibrahim; Samsuar Samsuar (Education and Learning Journal, 2022)
This study aims to determine the role of the Institute for Development and Development of Al-Islam and Kemuhammadiyahan (LP2AIK) in improving the ability to read the Qur'an for students of the Muhammadiyah Makassar Polytechnic. The type of research used is quantitative research with descriptive methods. The data collection methods used were observation, interviews, and questionnaires. Reading and writing the Koran and Tahsin, the supervisor also talks about the work from beginning to end, this is very good for Muhammadiyah Polytechnic students, where 61.11% of the population is the first best answer. Participate in the guide to reading the Koran. And researchers The study found that 59.88% of students said that their ability to read the Qur'an improved after following the instructions reading the Qur'an.